2001
DOI: 10.1037/0022-0167.48.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Where oh where are the specific ingredients? A meta-analysis of component studies in counseling and psychotherapy.

Abstract: Component studies, which involve comparisons between a treatment package and the treatment package without a theoretically important component or the treatment package with an added component, use experimental designs to test whether the component is necessary to produce therapeutic benefit. A meta-analysis was conducted on 27 component studies culled from the literature. It was found that the effect size for the difference between a package with and without the critical components was not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
353
2
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(369 citation statements)
references
References 57 publications
8
353
2
6
Order By: Relevance
“…Contemporary research suggests that about 45% of the variance of therapy outcomes is due to general factors of the therapeutic relationship (Lambert, 1992). By contrast, about 15% of the differences among therapeutic outcomes is due to specific theoretical approaches, although recent analyses sometimes put the specific effects lower still (Ahn & Wampold, 2001;Lambert, 1992). The remaining variance is due to client and chance factors (Krupnick et al, 1996).…”
Section: The Problem and Its Significancementioning
confidence: 99%
“…Contemporary research suggests that about 45% of the variance of therapy outcomes is due to general factors of the therapeutic relationship (Lambert, 1992). By contrast, about 15% of the differences among therapeutic outcomes is due to specific theoretical approaches, although recent analyses sometimes put the specific effects lower still (Ahn & Wampold, 2001;Lambert, 1992). The remaining variance is due to client and chance factors (Krupnick et al, 1996).…”
Section: The Problem and Its Significancementioning
confidence: 99%
“…Therapy, Spence [1984] and Totman [1979] amongst others argue, involves the creation of a narrative sufficiently compelling for the patient to enter into, where the match between the story and the 'listener' is more important than the truth of the tale. In a meta-analysis of psychotherapy 'component studies', that is, studies that pit a specific treatment against a treatment package without a component known or assumed to have therapeutic benefit, Ahn and Wampold [2001] found the "critical components" of key therapries did not have power significantly different from zero. They suggest the reasons is not that therapies are useless, but that there are useful elements common to all therapies.…”
Section: Lorementioning
confidence: 99%
“…The report recommends that research be conducted to identify and validate "elements" of psychosocial interventions, defined as "therapeutic activities, techniques, or strategies" (p. 3-1). The au-thors argue that this approach could be used to "establish optimal sequencing and dosing of elements" and "connect elements more precisely to purported mechanisms of change than is the case with an entire complex psychosocial intervention" (p. [3][4][5]. Unfortunately, little evidence supports the notion that multifaceted treatments will benefit from deconstruction or retain efficacy when disassembled.…”
mentioning
confidence: 99%
“…Studies do not support the hypothesis that psychotherapy elements are independently "active." Meta-analyses of dismantling trials (studies wherein investigators compare a treatment to the treatment minus an integral component) have not found effect sizes that differ significantly from zero [3,4] and effect sizes for additive studies (comparing a treatment to the treatment plus an element) are so small (d = .14) that clinical significance is very unlikely. [4] Thus, although the notion of identifying, separating, and recombining core elements to discover new brain circuits or improve outcomes is intellectually appealing, the extant evidence does not support the feasibility or efficacy of this methodology.…”
mentioning
confidence: 99%